Proceedings of GLOBECOM'96. 1996 IEEE Global Telecommunications Conference
DOI: 10.1109/glocom.1996.594454
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive OFDM for wideband radio channels

Abstract: capacity of a measured broadband radio channel is calculated An OFDM (orthogonal frequency division multiplexing) transmission system is simulated with time-variant transfer functions measured with a wideband channel sounder. The individual subcarriers are modulated with fixed and adaptive signal alphabets. Furthermore, a frequency-independent as well as the optimum power distribution are used. The simulations show that with adaptive OFDM, the required signal power for an error probability of can be reduced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
0
5

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(108 citation statements)
references
References 4 publications
(2 reference statements)
1
102
0
5
Order By: Relevance
“…Although the problem of optimal real-time subcarrier allocation has been extensively studied (see [4]- [14] and references therein), our work is philosophically different from most of literature: Often, in subcarrier allocation, an "instantaneous throughput" is maximized while assuming infinitely backlogged buffers; the algorithms are run periodically, to allow updates regarding channel variations and varying number of data streams. The problem with these techniques is that the scheduler fails to anticipate the impact of its allocation decision on the future state of the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the problem of optimal real-time subcarrier allocation has been extensively studied (see [4]- [14] and references therein), our work is philosophically different from most of literature: Often, in subcarrier allocation, an "instantaneous throughput" is maximized while assuming infinitely backlogged buffers; the algorithms are run periodically, to allow updates regarding channel variations and varying number of data streams. The problem with these techniques is that the scheduler fails to anticipate the impact of its allocation decision on the future state of the system.…”
Section: Introductionmentioning
confidence: 99%
“…each subcarrier receives equal power) instead of the optimal power spectrum [4]. The channel gain h ij can be mapped to the number of packets per time slot, c ij , that subcarrier i can potentially transmit for user j as [4]:…”
Section: A Numerical Comparisons and Simulationmentioning
confidence: 99%
“…The choice of the target BER has obviously quite an impact, as a lower target BER leads to higher SNR switching points per modulation type (and therefore to a lower physical layer throughput). Refer to [21] for an detailed discussion of the performance difference between adaptive modulation and bit loading.…”
Section: Dynamic Single-user Ofdmmentioning
confidence: 99%
“…One particular simple but still very efficient dynamic scheme is adaptive modulation, where the transmit power per sub-carrier is fixed and only the modulation type per sub-carrier is varied according to the SNR. In fact, in [21] it has been shown that adapting the modulation while keeping the transmit power fixed provides a large performance boost which is only marginally improved by also adapting the transmit power.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied the performance and have proposed possible solutions under imperfect CSI at the transmitter. Bit and power loading algorithms were pursued in [7][8][9][10][11][12][13][14], where partial CSI was utilized to adapt the constellation size and/or the power, adhering to a certain target bit error rate (BER) http://jwcn.eurasipjournals.com/content/2012/1/208 per subcarrier. However, the authors did not consider the effect of ICI.…”
Section: Introductionmentioning
confidence: 99%